2018
DOI: 10.21037/jtd.2018.04.163
|View full text |Cite
|
Sign up to set email alerts
|

Non-pyothorax-associated primary pleural lymphoma without pleural effusion in an immunocompetent patient: a case report and literature review

Abstract: Non-pyothorax-associated primary pleural lymphoma without pleural effusion in an immunocompetent patient: a case report and literature review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Our case showed a positive ‘pleural sandwich sign’ in contrast‐enhanced CT, in which the intercostal arteries are well visualized in the conglomerated pleural and chest wall masses. This sign has been reported in three previous reports of primary chest wall lymphomas occurring in patients without preceding pleural disease 7–9 . Kim et al reported that this sign is not seen in non‐lymphoma pleural tumours because of their rapid invasion of intercostal vessels 9 .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Our case showed a positive ‘pleural sandwich sign’ in contrast‐enhanced CT, in which the intercostal arteries are well visualized in the conglomerated pleural and chest wall masses. This sign has been reported in three previous reports of primary chest wall lymphomas occurring in patients without preceding pleural disease 7–9 . Kim et al reported that this sign is not seen in non‐lymphoma pleural tumours because of their rapid invasion of intercostal vessels 9 .…”
Section: Discussionmentioning
confidence: 60%
“…This sign has been reported in three previous reports of primary chest wall lymphomas occurring in patients without preceding pleural disease. 7 , 8 , 9 Kim et al reported that this sign is not seen in non‐lymphoma pleural tumours because of their rapid invasion of intercostal vessels. 9 This finding is likely to occur due to lymphoma infiltration to the perivascular interstitium without invading the vascular wall.…”
Section: Discussionmentioning
confidence: 99%
“…The present case has a survival of 9 years at list. We suppose that it is related to the good Performance Status (PS) and the preserved respiratory function of our patient [19].…”
Section: Discussionmentioning
confidence: 99%